Investigating the adhesion of encysted zoospores of the oomycete Phytophthora cinnamomi during the early infection of avocado - Van den Berg, Noelani (University of Pretoria, 2022)
Dissertation (MSc (Microbiology))--University of Pretoria, 2022.